Being multiracial in a virtual society: Seeking community and exploring identity. Issue 174 (5th November 2021) - Luna, Rachel H.
Abstract: This article presents an overview of current Internet and social media trends, followed by a description of online experiences for minoritized and Multiracial students. Implications for student affairs scholarship and practice are offered.